IMPLEMENTASI PELATIHAN APLIKASI ZOTERO DI PERPUSTAKAAN UNIVERSITAS MUHAMMADIYAH YOGYAKARTA BAGI MAHASISWA MAGISTER ILMU PEMERINTAHAN - Muhammad Erdiansyah Cholid Anjali; Zeni Istiqomah (UPT. Perpustakaan Universitas Muhammadiyah Ponorogo, 2019)
The purpose of this study is to describe how the implementation of the training zotero in Yogyakarta Muhammadiyah University Library. This research uses descriptive method qualitative approach. Data collection techniques in this study using observation, interviews, and documentation. The sampling technique used in the interview process is purposive sampling. The results showed that the material in the training conducted by the application zotero UMY library includes information about search, use zotero application for managing information, and utilization of information through the application zotero.